INNOVATIONS IN HIP ARTHROPLASTY: A COMPREHENSIVE REVIEW (International journal of medical sciences, 2026)
Hip arthroplasty represents a transformative procedure in modern orthopedic practice, significantly improving quality of life for patients suffering from chronic hip pain and mobility limitations. Despite substantial advancements over recent decades, challenges including implant wear, periprosthetic infections, and long-term durability necessitate continuous innovation. This comprehensive review analyzes recent innovations in hip arthroplasty, focusing on advancements in material science, surgical techniques, digital technologies, and implant design, while evaluating their clinical implications and future prospects. A systematic analysis and synthesis of contemporary scientific literature pertaining to innovations in hip arthroplasty was conducted, with particular emphasis on developments in material science, biomechanics, surgical robotics, three-dimensional printing technologies, and augmented reality applications. Significant innovations include the development of advanced bearing surfaces such as ceramic-on-ceramic, ceramic-on-polyethylene, and highly cross-linked polyethylene, which demonstrate superior wear characteristics and reduced osteolysis risk compared to traditional metal-on-polyethylene combinations [1, 2]. Contemporary material science advances encompass bioactive materials, novel titanium alloys, and enhanced polymer composites designed to improve osseointegration and reduce infection rates [2]. Surgical innovations incorporate artificial intelligence, augmented reality navigation systems, and robotic assistance, which enhance procedural accuracy, minimize soft tissue trauma, and accelerate postoperative recovery [3]. Three-dimensional printing technology enables patient-specific implants and instrumentation, facilitating improved preoperative planning, anatomical fit, and long-term stability through porous surface structures that promote osseointegration [4, 5]. Contemporary innovations in hip arthroplasty have substantially improved implant durability, surgical precision, and patient outcomes. Future developments including smart implants with integrated sensors, further artificial intelligence integration, and expanded three-dimensional printing applications promise continued advancement, though challenges related to cost, regulatory approval, and long-term data collection require multidisciplinary collaboration for successful implementation.